2018
DOI: 10.1080/10934529.2017.1422954
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and hydrological aspects of an evapotranspiration-constructed wetland combined system for household greywater treatment

Abstract: Constructed wetlands systems demand preliminary and primary treatment to remove solids present in greywater (GW) to avoid or reduce clogging processes. The current paper aims to assess hydraulic and hydrological behavior in an improved constructed wetland system, which has a built-in anaerobic digestion chamber (AnC), GW is distributed to the evapotranspiration and treatment tank (CEvaT), combined with a subsurface horizontal flow constructed wetland (SSHF-CW). The results show that both the plants present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…The peak values of ETP were near 40 mm/d and correlated with average temperatures 20-25 • C. These values for the spring and summer seasons fit with the findings of Pedescoll et al [64], who reported similar results for different plant species used in TWs in a Mediterranean climate similar to the one in the current study. Other authors, such as Headley et al [65] and Filho et al [66], reported ETP below 20 mm/d for horizontal subsurface flow TWs, which is similar to the values achieved in the present study. Thus, the results of water loss and ETP show that Za is a plant species with similar behavior compared with traditional plant species such as Schoenoplectus for use in vertical TWs for arid and Mediterranean climate conditions.…”
Section: Aridsupporting
confidence: 92%
“…The peak values of ETP were near 40 mm/d and correlated with average temperatures 20-25 • C. These values for the spring and summer seasons fit with the findings of Pedescoll et al [64], who reported similar results for different plant species used in TWs in a Mediterranean climate similar to the one in the current study. Other authors, such as Headley et al [65] and Filho et al [66], reported ETP below 20 mm/d for horizontal subsurface flow TWs, which is similar to the values achieved in the present study. Thus, the results of water loss and ETP show that Za is a plant species with similar behavior compared with traditional plant species such as Schoenoplectus for use in vertical TWs for arid and Mediterranean climate conditions.…”
Section: Aridsupporting
confidence: 92%
“…According to the results of this review Brazilian scientists are the most prolific authors within the region, with around 32% of the total production in the region and a contribution of 53 documents to this review. The information produced by Brazilian scientists dealing with CW covers a wide spectrum of topics, including papers describing the state-of-the-art constructed wetlands in the country [10,110], life-cycle analysis contributions [63], hydraulics [112], removal of recalcitrant pollutants [115], and other topics related to the performance of CWs operating under different conditions. Brazil is the only country that has reported research on the five different technologies analyzed.…”
Section: Most Productive In Terms Of Publications Regarding Cws Countmentioning
confidence: 99%
“…The role of the filling media and its capacity for phosphorus removal [116], and the removal of elements [165] has been reported. Some of the studies tackle hydraulics [71,111,128], clogging phenomena [112], kinetics for nutrient removal [47] and flow patterns [143]. Some studies deal with climatic effects, including systems in super-arid areas [125], and in tropical regions [14,130,140,144].…”
Section: Cw Technologies Reviewedmentioning
confidence: 99%
“…Further, studied the performance of biochar as substrates in VFCWs for enhancing the removal of contaminant from low C/N wastewaters with different influent strengths and reported that biochar VFCW, when compared to nonbiochar VFCW, showed higher removal of organic pollutants (85%), NH + 4 − N (39%), and TN (39%), especially at high influent strengths and moderate N 2 O emission was observed in biochar-added VFCWs under various influent strengths. Filho, Sobrinho, Steffen, Arias, and Paulo (2018) studied the performance of improved CW system consisting of built-in anaerobic digestion tank (AnC) followed by evapotranspiration and treatment tank (CEvaT), combined with an SSHFCW treating graywater. The results showed that planted CEvaT can be an attractive pretreatment alternative for CW systems, reducing clogging issues and consequently lowering operation and maintenance demands with an applied organic load of 32 gCOD/m 2 day and hydraulic loading rate of approximately 80 mm/day.…”
Section: Annual Literature Reviewmentioning
confidence: 99%